2014
DOI: 10.1002/asna.201312011
|View full text |Cite
|
Sign up to set email alerts
|

Combining optical spectroscopy and interferometry

Abstract: Modern optical spectrographs and optical interferometers push the limits in the spectral and spatial regime, providing important new tools for the exploration of the universe. In this contribution I outline the complementary nature of spectroscopic & interferometric observations and discuss different strategies for combining such data. Most remarkable, the latest generation of "spectro-interferometric" instruments combine the milliarcsecond angular resolution achievable with interferometry with spectral capabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Spatially and spectrally resolved investigations with the VLTI/MIDI instrument revealed radial gradients in the dust minerology and found that the crystallinity is higher in the inner few au of the disk, supporting theories of grain growth (van Boekel et al 21 ). The hydrocarbon-related emission is located in the gap region (V1247 Ori: Kraus et al 22 ) and in the outer disk (Olofsson et al 11 ).…”
Section: Protoplanetary Disk Structure and Disk Physicsmentioning
confidence: 99%
“…Spatially and spectrally resolved investigations with the VLTI/MIDI instrument revealed radial gradients in the dust minerology and found that the crystallinity is higher in the inner few au of the disk, supporting theories of grain growth (van Boekel et al 21 ). The hydrocarbon-related emission is located in the gap region (V1247 Ori: Kraus et al 22 ) and in the outer disk (Olofsson et al 11 ).…”
Section: Protoplanetary Disk Structure and Disk Physicsmentioning
confidence: 99%